2018
DOI: 10.2334/josnusd.17-0005
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of 2-arachydonoylgycerol degradation attenuates orofacial neuropathic pain in trigeminal nerve-injured mice

Abstract: Current therapeutics are not effective for orofacial neuropathic pain, and better options are needed. The present study used inferior orbital nerve (ION)-injured mice to investigate the effect of inhibiting monoacylglycerol lipase (MAGL), an enzyme that degrades the major endocannabinoid 2-arachydonoylgycerol (2-AG) in orofacial neuropathic pain. The head-withdrawal threshold to mechanical stimulation of the whisker pad was reduced on days 3, 5, and 7 after ION injury. Injection of JZL184, a selective inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 67 publications
1
17
0
Order By: Relevance
“…We also observed that MAGL immunoreactive neurons were increased in the Vc and upper cervical spinal cord (C1-C2) under the neuropathic pain condition, and this effect was reduced after administration of JZL184 [258]. These observations suggest that 2-AG may be increased in the Vc and C1-C2 areas under neuropathic pain conditions ( Figure 1) and rapidly degraded by MAGL, as indicated by the increased MAGL immunoreactivity [258]. 2-AG can be released from postsynaptic neurons by exaggerated presynaptic neuronal activity because of nerve injury [21,70,258] (Figure 1), which can be considered as the body's autoprotective/defense mechanism for pain control [21,61,68,69].…”
Section: Route Of Administrationmentioning
confidence: 64%
See 3 more Smart Citations
“…We also observed that MAGL immunoreactive neurons were increased in the Vc and upper cervical spinal cord (C1-C2) under the neuropathic pain condition, and this effect was reduced after administration of JZL184 [258]. These observations suggest that 2-AG may be increased in the Vc and C1-C2 areas under neuropathic pain conditions ( Figure 1) and rapidly degraded by MAGL, as indicated by the increased MAGL immunoreactivity [258]. 2-AG can be released from postsynaptic neurons by exaggerated presynaptic neuronal activity because of nerve injury [21,70,258] (Figure 1), which can be considered as the body's autoprotective/defense mechanism for pain control [21,61,68,69].…”
Section: Route Of Administrationmentioning
confidence: 64%
“…Trigeminal nerve injury was observed to induce neuropathic pain symptoms in the orofacial area [258,[263][264][265]. Systemic administration of the compound attenuated mechanical allodynia 2 h after administration [258]. We also observed that MAGL immunoreactive neurons were increased in the Vc and upper cervical spinal cord (C1-C2) under the neuropathic pain condition, and this effect was reduced after administration of JZL184 [258].…”
Section: Route Of Administrationmentioning
confidence: 67%
See 2 more Smart Citations
“…JZL184 acts as a MAGL-specific inhibitor [229], which allows differentiation from FAAH-inhibition mediated effects [231], and has been shown to produce analgesia in various pain assays [229,[232][233][234][235][236][237]. In a mouse model of orofacial neuropathic pain, induced via injury of the inferior orbital nerve, JZL184 reduced pain (increased threshold to mechanical stimulation) 2 h following administration [231].…”
Section: Novel Approaches To Modulate the Ocular Ecs: Cannabinoid Recmentioning
confidence: 99%